MENJADI ORANG TUA BIJAK DI ERA DIGITAL: PSIKOEDUKASI ORANG TUA SISWA SEKOLAH KRISTEN YUSUF - Sahrani, Riana; Mursalim, Tania; Imanuel , Dastin (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The challenges of parenting children and adolescents in the digital era are becoming increasingly complex, particularly regarding the use of digital technology, which is not matched by adequate parenting literacy among parents. Parents often struggle to decide between being a “good” or a “right” parent when dealing with their children's digital behavior. This community service program aimed to enhance parents' capacity to establish healthy, adaptive, and empathetic digital parenting practices. Unlike similar programs that focus solely on device control and screen-time limitations, this activity introduced a reflective and comprehensive psychoeducational approach by integrating digital literacy, empathetic communication, emotional regulation, and stress management strategies. The seminar was delivered by lecturers and graduate students from the Faculty of Psychology, Tarumanagara University, through three stages: pre-test, material delivery, case discussion, and post-test. The pre-test results from 27 participants showed an average score of 86, which increased to 94 in the post-test completed by 10 participants, along with a decrease in standard deviation from 13.34 to 10.75. These results indicate that the reflective psychoeducational approach successfully improved participants’ understanding in a more evenly distributed and in-depth manner. In conclusion, a reflective and case-based psychoeducation model can serve as an effective intervention to better prepare parents to face the challenges of raising adolescents wisely and with digital awareness. ABSTRAK Tantangan pengasuhan anak dan remaja di era digital semakin meningkat, khususnya dalam penggunaan teknologi digital yang belum diimbangi dengan literasi pengasuhan yang memadai di kalangan orang tua. Orang tua sering kali kebingungan dalam menentukan sikap antara menjadi “baik” atau “benar” dalam menghadapi dinamika perilaku anak di dunia digital. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kapasitas orang tua dalam membangun pola pengasuhan digital yang sehat, adaptif, dan empatik. Berbeda dari kegiatan sejenis yang hanya menekankan pada kontrol perangkat dan pembatasan waktu layar, kegiatan ini menawarkan pendekatan reflektif dan menyeluruh melalui seminar psikoedukatif yang mengintegrasikan aspek literasi digital, komunikasi empatik, regulasi emosi, dan strategi pengelolaan stres. Seminar dilaksanakan oleh dosen dan mahasiswa Magister Psikologi Universitas Tarumanagara dalam tiga tahapan: pre-test, penyampaian materi, diskusi kasus, dan post-test. Hasil pre-test dari 27 peserta menunjukkan skor rata-rata 86, yang meningkat menjadi 94 pada post-test dari 10 peserta, dengan penurunan standar deviasi dari 13,34 menjadi 10,75. Hasil ini menunjukkan bahwa pendekatan reflektif dalam psikoedukasi dapat meningkatkan pemahaman orang tua secara lebih merata dan mendalam. Kesimpulannya, psikoedukasi berbasis refleksi dan studi kasus nyata dapat menjadi model intervensi yang efektif untuk meningkatkan kesiapan orang tua dalam menghadapi tantangan pengasuhan remaja di era digital secara lebih bijaksana dan sadar teknologi.